Pengaruh Model pembelajaran Giving Question and Getting Answer Terhadap Hasil Belajar Tematik Siswa Sekolah Dasar - Samrani Samrani; Nursalam Nursalam; Suardi Suardi (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
The main problem in this research is that learning activities are still focused on the teacher, students lack focus in learning and often complain of being bored in learning, resulting in thematic learning outcome skills. This research aims to determine the effect of the Giving Question and Getting Answer learning model on thematic learning outcomes of class IV students at SDN 144 Sumpang Ale, Sinjai Regency. The type of research used in this research is Pre-Experimental Design and is a quantitative type of research. The sample in this study was 21 students. Data collection techniques were carried out using learning results tests and observation sheets. The data analysis technique in this research is descriptive data analysis technique and T-Test. The research results showed that the thematic learning results before implementing the Giving Question and Getting Answer learning model in the pretest were with an average score of 61.4. Meanwhile, the posttest increased with an average score of 80.5. The results of the t-test analysis regarding the influence of the Giving Question and Getting Answer learning model on student learning outcomes show that the significance value obtained is good, namely the influence of the Giving Question and Getting Answer learning model on thematic learning outcomes (Sig = 0.016) is smaller than the alpha value The set value is 0.05 (0.016 < 0.05). Based on the results obtained, it can be concluded that Ho is rejected and H1 is accepted, which states that there is an influence of the use of the Giving Question and Getting Answer learning model on the thematic learning outcomes of class IV students at SDN 144 Sumpang Ale, Sinjai Regency.